News framing and escalation of ethno-political antipathies issues: a quantitative content analysis of newspapers / Sadiq Mohammed and Syarizan Dalib - Mohammed, Sadiq; Dalib, Syarizan (2017)
Ethno-political antipathies issues such as Farmers/Herdsmen clashes and post-election violence have persisted and lingered for decades in developing countries. In view of these clashes, ethno-political groups are wandering the path of hatred and irreconcilable for decades. Hence, this paper investigates and discloses the patterns of news framing on these issues in Nigerian newspapers. News headlines and story lead paragraphs from three Nigerian national daily newspapers, (the Daily Trust, Nigerian Tribune, and the Sun newspapers) were content analyzed. The findings indicated three main patterns of news framing which are stereotypes, favoritism, and ethnic apathy during the period under study. The three newspapers examined correlated with factors such as ownership, proximity, and accepted those ideas of political elites in framing ethno-political antipathies in Nigeria. Therefore, this study suggests that newspapers have apparently adopted both positive and negative labeling/depictions as the elements that shape their regional and ethno-political proclivity. The framing of antipathies seemed to exploit national integration through acceptance of this political rhetoric. This study is beneficial for policy makers to construe the causes, consequences, and offered solutions on proposed reviews of existing media laws within Nigeria's political entity. An investigation of issues on ethno-political antipathies in other genres of mass media like radio is recommended for future research direction.